Mycobacterium chimaera infection following cardiac surgery in the United Kingdom: clinical features and outcome of the first 30 cases. (November 2018) - Scriven, J.E.; Scobie, A.; Verlander, N.Q.; Houston, A.; Collyns, T.; Cajic, V.; Kon, O.M.; Mitchell, T.; Rahama, O.; Robinson, A.; Withama, S.; Wilson, P.; et al.
Abstract: Objectives: Mycobacterium chimaera infection following cardiac surgery, due to contaminated cardiopulmonary bypass heater–cooler units, has been reported worldwide. However, the spectrum of clinical disease remains poorly understood. To address this, we report the clinical and laboratory features, treatment and outcome of the first 30 UK cases. Methods: Case note review was performed for cases identified retrospectively through outbreak investigations and prospectively through ongoing surveillance. Case definition was Mycobacterium chimaera detected in any clinical specimen, history of cardiothoracic surgery with cardiopulmonary bypass, and compatible clinical presentation. Results: Thirty patients were identified (28 with prosthetic material) exhibiting a spectrum of disease including prosthetic valve endocarditis (14/30), sternal wound infection (2/30), aortic graft infection (4/30) and disseminated (non-cardiac) disease (10/30). Patients presented a median of 14 months post surgery (maximum 5 years) most commonly complaining of fever and weight loss. Investigations frequently revealed lymphopenia, thrombocytopenia, liver cholestasis and non-necrotizing granulomatous inflammation. Diagnostic sensitivity for a single mycobacterial blood culture was 68% but increased if multiple samples were sent. In all, 27 patients started macrolide-based combination treatment and 14 had further surgery. To date, 18 patients have died (60%) a median of 30 months (interquartile range 20–39 months) after initial surgery. Survival analysis identified younger age, mitral valve surgery, mechanical valve replacement, higher serum sodium concentration and lower C-reactive protein as factors associated with better survival. Conclusions: Mycobacterium chimaera infection following cardiac surgery is associated with a wide spectrum of disease. The diagnosis should be considered in all patients who develop an unexplained illness following cardiac surgery.